Generative AI and the Future of Creativity: Threat or Catalyst for Innovation? - Umar Umar; M Bambang Purwanto (Foreign Language Instruction Probe, 2025)
The advent of generative AI has sparked widespread debate about its implications for creativity and innovation. This article explores the dual nature of generative AI as both a potential threat and a catalyst for creative progress. While AI systems are capable of producing art, literature, music, and design with remarkable efficiency, concerns have emerged regarding the erosion of human-centered creativity and the risk of homogenization in artistic expression. On the other hand, proponents argue that AI serves as a powerful tool that expands the boundaries of creativity by augmenting human capabilities, fostering new forms of artistic collaboration, and accelerating innovation in various fields. This article critically examines both perspectives, analyzing the role of generative AI in shaping the future of creativity. It highlights the need for ethical frameworks and a balanced approach to integrating AI technologies, ensuring that human imagination remains central to creative endeavors while leveraging AI’s potential for transformative innovation.